ChemInform Abstract: Ca18.75Li10.5 [Al39N55]:Eu2+ — Supertetrahedron Phosphor for Solid‐State Lighting. Issue 18 (April 2016) - Wagatha, Peter; Pust, Philipp; Weiler, Volker; Wochnik, Angela S.; Schmidt, Peter J.; Scheu, Christina; Schnick, Wolfgang
Abstract: Ca18.75 Li10.5 [Al39 N55 ]:Eu 2+ (0.5 mol%) is prepared by hot pressing of stoichiometric amounts of Li3 N, CaH2, AlN, and EuF3 (Mo‐lined corundum crucibles in an isostatic press, 51.7 MPa N2, 1250 °C, 5 h).